Precarização do trabalho docente: as condições de trabalho do professor de ciências em classes multisseriadas. - SILVA, Ana Lúcia Barreto da (2021)
This article aims to discuss the precariousness of teaching work in rural schools, emphasizing the working conditions of the science teacher in multi-series classes, which resist in the midst of the adverse conditions that shape the reality of rural schools. The methodology used was based on qualitative research, having as data collection technique structured interviews and application of open questionnaires, through which we obtained the testimonies of the science teacher of the Municipal School of Fundamental Education Dream of Child, of the pedagogical coordinator who orient the work in the school related to the discipline of Sciences and director of education of the municipality of Pacajá-Pa. The research reveals the precarious conditions in which teachers have been working in a multi-serialized class, such as the precarious state of the school infrastructure, the lack of specific continuing education for the science teacher working in these classes, and the difficulties faced to work the content of sciences in class composed of different series, mainly due to the lack of adequate didactic resources and quantity to work in multi-series classes. As a main conclusion the study points out that the work of the science teacher has been based on the use of the urban serial model of teaching, and it is necessary to discuss specific teaching practices to ensure more favorable conditions for teaching work in multi-series classes.